Knowledge Management Strategy Employed In A SME: The Case Of A Building Materials Supplier - Shackelford, Adam; Sun, Peter Y.T. (Journal of Knowledge Management Practice, 2009)
The purpose of this paper is to investigate the knowledge management strategy of a small to medium enterprise (SME), and the consequences of a misplaced strategy. The methodology employed for this study applied three triangulated techniques for data collection in the field. The findings showed that management level and staff level employed different strategies to manage knowledge. Management focused on more formal IT systems and tools to manage knowledge, with a focus on explicit knowledge management. Frontline staff depended more heavily on communities of practice and learning-by-doing and to manage their knowledge. This resulted in many frontline staff finding little value for the standard technological tool and systems implemented. There are few empirical studies that look at knowledge management strategies within SMEs. This article, to some degree, fills this knowledge gap.
Keywords: Knowledge management; Knowledge management strategies; Explicit knowledge; Tacit knowledge; Small and medium Enterprise